DOI: 10.17077/etd.o077ceim
|View full text |Cite
|
Sign up to set email alerts
|

Who do you think you are? constructing self/identity in women's rugby through aggression, control and unacceptable behavior

Abstract: Who do you think you are? constructing self/identity in women's Who do you think you are? constructing self/identity in women's rugby through aggression, control and unacceptable behavior rugby through aggression, control and unacceptable behavior ABSTRACT Some behaviors in sport may be labeled: bad, unnecessary and distasteful. Sport psychologists have used concepts of aggression to understand and lessen these behaviors.To date, most research has conceptualized aggression as a product of individual cognition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 124 publications
(409 reference statements)
0
4
0
Order By: Relevance
“…This research draws on feminist poststructuralist theorising and particularly in the works of Butler (1990Butler ( , 1993, Foucault (1972Foucault ( , 1977Foucault ( , 1978, and Weedon (1997). Critical scholars of sport have proposed feminist poststructuralist theory as a suitable framework for examining the experiences and identities of female athletes, as it offers tools for tracing the complex processes through which women become subjected to specific (gendered and culturally appropriate) ways of understanding themselves and others (Baird 2010;Kavoura 2018;McGannon and Busanich 2010;Ryba and Wright 2010). Following the above-mentioned authors, we adopt a particular understanding of the concepts of identity, discourse, subject 121 position, and subjectivity.…”
Section: Theoretical Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…This research draws on feminist poststructuralist theorising and particularly in the works of Butler (1990Butler ( , 1993, Foucault (1972Foucault ( , 1977Foucault ( , 1978, and Weedon (1997). Critical scholars of sport have proposed feminist poststructuralist theory as a suitable framework for examining the experiences and identities of female athletes, as it offers tools for tracing the complex processes through which women become subjected to specific (gendered and culturally appropriate) ways of understanding themselves and others (Baird 2010;Kavoura 2018;McGannon and Busanich 2010;Ryba and Wright 2010). Following the above-mentioned authors, we adopt a particular understanding of the concepts of identity, discourse, subject 121 position, and subjectivity.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…The neoliberal discourses emphasise individual responsibility and ignore cultural barriers, such as those produced by gender hierarchies (Brunila et al 2011;Brunila and Ylöstalo 2015). In similar vein, DC policies and practices ignore the gender inequalities that exist in the male-dominated sport fields (Baird 2010;Halbert 1997;Kavoura, Ryba, and Chroni 2015;Kavoura et al 2018;Ryba et al 2015;Skrubbeltrang 2018;Skrubbeltrang et al 2018) and instead emphasise importance for the individual of working hard and making the 'right choices' (Pless 2014, 236). Being subjectified to the forces of these discourses, and to the belief that gender equality is now guaranteed in Finland (Brunila and Ylöstalo 2015), the female Finnish judo athletes downplayed the role of gender in their judo careers.…”
Section: Gendered Selvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that acts of aggression are incorporated both in rugby and handball play. (Baird, 2010) In handball, rugby and in other sports that involve opposition-collaboration, there are potentially dangerous that game situations occur in the course of a game or training sessions (Abeza, Bravo, & Olmedilla, 2006, p. 110). Therefore, there are specific common behavioral trends like: extroversion, cooperation, ascending, and toughness.…”
Section: Introduction Background and Significancementioning
confidence: 99%